INJURY RISK IN KITESURFING: A LITERATURE REVIEW OF THE MOST COMMON TRAUMA PATTERNS AND SAFETY IMPLICATIONS - Bartosz Żegleń; Patryk Macuk; Anna Leśniewska; Julia Tarnowska; Filip Szydzik; Michał Gniedziejko; Dominika Nowak; Marcin Sawczuk; Adam Zarzycki; Aleksandra Gradek (International Journal of Innovative Technologies in Social Science, 2025)
Objective: This review aims to synthesize current evidence on the injury epidemiology of kitesurfing, focusing on common trauma patterns, underlying risk factors, and the effectiveness of safety strategies. Methods: A systematic literature search was conducted in PubMed and SPORTDiscus for articles published between 2000 and 2024. Studies were included if they reported original quantitative data on kitesurfing-related injuries, including incidence, anatomical distribution, severity, or safety practices. A narrative synthesis was applied due to methodological heterogeneity. Results: Injury incidence rates ranged from 4.3 to 10.5 per 1, 000 hours of kitesurfing exposure. The most frequently injured areas were the lower extremities, particularly the foot, ankle, and knee. Common injury types included abrasions, sprains, and soft-tissue trauma, with serious injuries such as spinal fractures and head trauma occurring less frequently but with notable severity. Experience level was inversely correlated with injury risk, while environmental factors—such as wind instability and shallow water—significantly contributed to accidents. Although quick-release harness systems are now widely adopted (97%), their real-time use during injury events remains low (7.3%). Helmet (4%) and impact vest (19.5%) usage remains limited despite recommendations. Conclusion: Kitesurfing presents a distinct injury profile influenced by biomechanical demands, environmental variables, and user behavior. While most injuries are mild and permit rapid return to sport, severe cases still occur, underscoring the need for improved safety education, structured training, and increased protective gear compliance. Future research should emphasize standardized reporting and long-term outcome tracking to better inform injury prevention strategies.